(untitled) (Global Journal of Management and Business Research, 2019)
Nowadays due to the advancement of technology students waste much of their study time in using social media rather than dealing with academic issues As a result the intent of this study was to investigate the effects of social media on students reading habits at Oda Butum University Ethiopia The study used descriptive research methodology using cross-sectional data collected from both primary and secondary sources through qualitative and quantitative research techniques To answer the research questions the researchers collected primary data from 280 students and also FGD was administered to further elaborate cases that are not clear during data collection period from respondents In this research the output of the data collected from students showed that most students preferred to use Facebook and YouTube to follow their friends posting and to watch video contents of different programs respectively Furthermore the data output revealed that students spent an average of 6 10 hours and 7 24 birr per day in using different social media accounts than dealing with studying their academic subject matters